2015
DOI: 10.1039/c4cc09012h
|View full text |Cite
|
Sign up to set email alerts
|

Chiral recognition of Arg based on label-free PET nanochannel

Abstract: Herein, we design a label-free PET nanochannel for enantioselective recognition of Arg by adding bovine serum albumin (BSA) as chiral selector. This method does not require modification on the channel surface and has applicability for fabricating other chiral sensors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 28 publications
0
49
0
Order By: Relevance
“…Such a great property is very useful for building a 4 highly sensitive and specific biosensor. Therefore, it is desirable to develop the nanochannel-based biosensor for high sensitive and specific detection of biomolecules (Sun et al, 2014;Liu et al, 2015;Sun et al, 2015;Gao et al, 2015;Wang et al, 2015;Sun et al, 2012;Xu et al, 2015;.…”
Section: Introductionmentioning
confidence: 99%
“…Such a great property is very useful for building a 4 highly sensitive and specific biosensor. Therefore, it is desirable to develop the nanochannel-based biosensor for high sensitive and specific detection of biomolecules (Sun et al, 2014;Liu et al, 2015;Sun et al, 2015;Gao et al, 2015;Wang et al, 2015;Sun et al, 2012;Xu et al, 2015;.…”
Section: Introductionmentioning
confidence: 99%
“…When there were S‐Npxs in solution, the aggregated AuNPs blocked ion flux in the nanochannel with a narrow tip, which led to the decline of ionic current (presented in Figure c) . With the same principle, they also realized the chiral‐recognition by using BSA as the functional molecules in nanochannels . The chiral‐recognitions of the small biomolecules was also introduced into the selective transport for nanochannels/nanopores.…”
Section: Featuresmentioning
confidence: 97%
“…The response processes with the functional biomolecules are, thereby, confined in the nanochannels/nanopores. Sun et al added BSA as chiral probes for the recognition of analytes in the PET conical nanochannels with tip diameter of about 16 nm and base diameter of about 520 nm . In their system, the BSA just were injected in the solution shown in Figure b.…”
Section: Functionalization Techniques Of Solid‐state Ion Nanochannelsmentioning
confidence: 99%
See 1 more Smart Citation
“…[27][28][29] Initially,f luorescence titration and infrared spectroscopy revealed that BSA has chiral selectivity toward cysteine enantiomers ( Figure S1-S3 in the Supporting Information). [27][28][29] Initially,f luorescence titration and infrared spectroscopy revealed that BSA has chiral selectivity toward cysteine enantiomers ( Figure S1-S3 in the Supporting Information).…”
mentioning
confidence: 99%